معضلة التقليد والتسييس قبل التفكير والتأسيس للعلوم الاجتماعية العربية: العلوم السياسية والعلاقات الدولية انموذجاً - بولبنان, زين العابدين (University of Eloued جامعة الوادي, 2016)
تطرح هذه الورقة إشكالية ابيستيمولوجية تتعلق بمدى إمكانية إعادة بناء هوية مستقلة لعلم سياسة عربي. ولا جرم أن بلوغ هذا المقصد لا يكون إلا بالتفكير والتدبر في مصادر تأسيس الاسلام و مجتمعاته، مع الاجتماع العلمي حولها بفهوم مشتركة لعقول ترشد معرفياً نحو الحق، ومقاربة الحقيقة، وموافقة الشرع فيما يصدر من ظواهر سياسية في واقع الأمر؛ ليتسنى بذلك إحداث قطيعة مع ممارسة التقليد للمعطى المعرفي المحكوم، و المسيّس من جهة الغرب، أو ما يمكن وسمه بـ"سياسة علم السياسة". ويبقى التأكد من تحقق هذا المسعى، موثوقاً باختبار الافتراض الذي يقول بتحدي الشرعية الفكرية والهوية الأمريكية لعلم السياسية، علاوة على تحدي المشروعية المؤسساتية الدولية لمساقات العلم والتدريس والبحث فيه This paper poses an epistimological problematic regarding the extent of the possibility of reconstruction an independent identity for Arabic political science. this aim Can only be acheive after to thinking and reflecting on the sources of founding Islam and their communities, with meeting scientifically around it by joint minds which guided cognitively toward the right, to approach the truth and non-infringement of the islamic law As it appears from the political phenomena, in fact. So, that it can make a break with the cognitive given governed and politicized by the west, or what could be termed as "politics of political science". It remains sure to achieve this aim Relates to test the assumption that says of challenging the legitimacy of American intellectual and identity of political science, as well as the challenge of international institutional legitimacy to science courses and teaching and research
Dilemma of Imitation and Politicization before Thinking and Establishing of the Arab Social Sciences -A case study: Political Sciences and International Relations
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: التقليد، التسييس، التفكير، التأسيس، العلوم الاجتماعية والسياسية العربية; Imitation, Politicization, Thinking, Establishing, The Arab Social and political Sciences.